Some rituals of the uigurs in the fergana valley - Валиханова, Gulnara (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article is devoted to the traditions of the Uygurs connected with tea. The author described a number of Uyghur ceremoniesand systematized them